2010
DOI: 10.2165/11531570-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Abuse Potential of Benzodiazepines from a Prescription Database Using ‘Doctor Shopping’ as an Indicator

Abstract: The DSI can be used to assess the relative abuse liability of benzodiazepines and to detect signals of new patterns of abuse in settings where centralized records of prescription or deliveries are available for the great majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 27 publications
0
70
0
Order By: Relevance
“…Alprazolam was identified at least once in every participating country, but its potential for abuse in comparison with other benzodiazepines remains under discussion [1]. Since the 1990s, flunitrazepam has been particularly abused in France among opioid-dependent individuals treated with buprenorphine [7,24]. However, it is now one of the less frequently prescribed benzodiazepines in France [13,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alprazolam was identified at least once in every participating country, but its potential for abuse in comparison with other benzodiazepines remains under discussion [1]. Since the 1990s, flunitrazepam has been particularly abused in France among opioid-dependent individuals treated with buprenorphine [7,24]. However, it is now one of the less frequently prescribed benzodiazepines in France [13,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1990s, flunitrazepam has been particularly abused in France among opioid-dependent individuals treated with buprenorphine [7,24]. However, it is now one of the less frequently prescribed benzodiazepines in France [13,24,25]. Griffiths and Johnson [26] noted in their review that flunitrazepam and diazepam are the two benzodiazepines with the highest potential for abuse, as also seen in Sweden [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that, to the best of our knowledge, no systematic review of the literature on the misuse and dependence on benzodiazepines in the EU has been published until now. Nevertheless, for a small sample of the European literature on benzodiazepine misuse and dependence, see references [7,8,9,10,11,12,13,14,15,16,17,18,19]. Additionally, the misuse of anabolic steroids in the context of sports has also been excluded.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, 98% of these prescriptions were issued by one specific physician and dispensed by one specific pharmacy. [26,27] No study in France has reported this. However, an American study on the Researched Abuse Diversion and Addiction-Related Surveillance (RADARS) System Program reports 314 calls to Poison Centers between 2003 and 2007 (4% of all calls) in which both liquid and tablet methadone were ingested.…”
Section: Discussionmentioning
confidence: 99%